Analisis Penggunaan Modal Kerja Terhadap Profitabilitas Perusahaan Pada PT.Indofood Sukses Makmur Tbk Tahun 2019 – 2021 - Sri Retnaning Rahayu; Ardiansyah Japlani; Febria Ayu Puspita Ningrum (Jurnal Manajemen DIVERSIFIKASI, 2024)
The purpose of this study was to determine whether there is an influence of cash turnover, inventory turnover, and inventory turnover on profit margins at PT. Indofood Sukses Makmur, Tbk in 2019-2021. This type of research is descriptive research using a quantitative approach and using secondary data, namely data obtained from materials available in books, and other sources that are relevant to this research and will assist in processing the company's financial data obtained. The data analysis technique used in this study is panel data which is a combination of time series data and cross section data. Therefore, panel data has a combination of characteristics, namely data consisting of several objects and covering several periods of time. The results of the study show that cash turnover does not significantly affect profit margin at PT Indofood Sukses Makmur Tbk in 2019-2021. Receivable turnover has a negative and significant effect on profit margins. Inventory turnover has a positive and significant impact on profit margins at PT Indofood Sukses Makmur Tbk. Cash turnover, accounts receivable turnover, and inventory turnover have no simultaneous effect on profit margins.